Social Innovation For Health Research: Development of the SIFHR Checklist - Kpokiri, Eneyi E.; Chen, Elizabeth; Li, Jingjing; Payne, Sarah; Shrestha, Priyanka; Afsana, Kaosar; Amazigo, Uche; Awor, Phyllis; de Lavison, Jean-Francois; Khan, Saqif; Mier-Alpaño, Jana; Ong, Alberto; et al. (PLOS Medicine, 2021)
Background Social innovations in health are inclusive solutions to address the healthcare delivery gap that meet the needs of end users through a multi-stakeholder, community-engaged process. While social innovations for health have shown promise in closing the healthcare delivery gap, more research is needed to evaluate, scale up, and sustain social innovation. Research checklists can standardize and improve reporting of research findings, promote transparency, and increase replicability of study results and findings. Methods and findings The research checklist was developed through a 3-step community-engaged process, including a global open call for ideas, a scoping review, and a 3-round modified Delphi process. The call for entries solicited checklists and related items and was open between November 27, 2019 and February 1, 2020. In addition to the open call submissions and scoping review findings, a 17-item Social Innovation For Health Research (SIFHR) Checklist was developed based on the Template for Intervention Description and Replication (TIDieR) Checklist. The checklist was then refined during 3 rounds of Delphi surveys conducted between May and June 2020. The resulting checklist will facilitate more complete and transparent reporting, increase end-user engagement, and help assess social innovation projects. A limitation of the open call was requiring internet access, which likely discouraged participation of some subgroups. Conclusions The SIFHR Checklist will strengthen the reporting of social innovation for health research studies. More research is needed on social innovation for health.
Table 2 - intéressante à l’étape d’organiser son projet
Keywords: Innovation inclusive; Innovation sociale; Libre accès; Santé